Medication Non-Compliance in Patients with Schizophrenia Due To Familial, Environmental and Socio-Cultural Factors - Rizwan Farooq, Taimur Khan, Muntazir Mehdi, Unaiza Jawad, Shafqat Huma, Madiha Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: In schizophrenia, non-compliance with treatment leads to the disease burden in the community. It is considered as a challenge worldwide due to the need for long-term treatment and additional associated factors in Schizophrenia. Aim: The goal of the study is to identify patients with treatment non-compliance in schizophrenia and determine the related factors from environmental, socio-cultural and familial perspectives. Place and Duration: The study was carried out at the department of Behavioral Sciences, PGMI /AMC / LGH Lahore, Pakistan, from November 2021 to April 2022. Methods: The study included 100 patients with non-compliance to treatment in schizophrenia who visited the relevant psychiatric departments. For the research a descriptive cross-sectional design was chosen with non-random, purposive sample selection technique being utilised. Prior to the study, ethical approval from the authorities and informed consent from patients were obtained. Educated patients completed questionnaires whereas uneducated patients asked their relatives to provide such information on questionnaires. Results: Out of 100 participants, 56 were males and 44 were females, with a ratio of 1.4:1. The participants mean age was 32.25 ± 11.1. About 23% of them were uneducated, and above sixty percent (61%) had a family income < 20,000 PKR rupees per month. A substantial percentage of family-members (15%) were unaware of their role and that of their family members, and the majority (77%) stated that people made a negative contribution. Factors contributing to treatment non-compliance included belief as a major life event (6%), perception about the disease being incurable (25%), lack of nearby treatment access (76%), migration (8%), forgetting an appointment with medical professional (18%), discontinuation of medication on the advice of a faith healer (16%), discontinuation of medication due to social stigma (14%), no follow-up being arranged (22%), and refusal to continue treatment (13%). Conclusions: The study aimed to identify the possible reasons for medication non-compliance in patients of schizophrenia from environmental, socio-cultural and familial perspectives. Many factors have been recognised that contribute indirectly or directly to the treatment non-compliance. Keywords: Non-Compliance, Compliance and Schizophrenia